Special topics in drug discovery - Chen, Taosheng; Chai, Sergio C. (Intech, Croatia, 2017)
Drug discovery involves multiple disciplines, technologies, and approaches. This book selects important topics related to drug discovery, including emerging tool (Chapter 1), cutting-edge approaches (Chapters 2, 3, and 4), examples of specific therapeutic area (Chapter 5), quality control in drug development (Chapter 6), and job and career opportunities in the pharmaceutical sector, a topic rarely covered by other books (Chapter 7). This book draws knowledge from experts actively involved in different areas of drug discovery from both industrial and academic settings. We hope that this book will facilitate your efforts in drug discovery.
Autobioluminescent cellular models for enhanced drug dicovery -- Going small : using biophysical screening to imlpement fragment based drug discovery -- Chemical similarity networks for drug discovery -- Complex high-content phenotypic screening -- Schistosomiasis : setting routes for drug discovery -- QbD implementation in biotechnological product developmetn studies -- Job and career opportunities in the Pharmecueutcial sector --
Includes bibliographical references.
Keywords: PHARMACOGNOSY; TECHNOLOGY, PHARMACEUTICAL; CHEMISTRY, PHARMACEUTICAL